2022
DOI: 10.3389/fmed.2022.876864
|View full text |Cite
|
Sign up to set email alerts
|

Beyond QuantiFERON-TB Results, the Added Value of a Weak Mitogen Response

Abstract: IntroductionWhile QuantiFERON-TB gold (QFT) is frequently used, little attention is paid to the mitogen response. How it could be impacted and associated with outcomes is poorly known.MethodsRetrospective, case-control study in hospitalized patients who underwent QFT testing in two hospitals between 2016 and 2019. We defined two groups of cases with either negative [interferon (IFN)-γ ≤ 0.5 IU/ml, official threshold] or weak (0.5–2 IU/ml) mitogen response, and one group of controls with normal (>2 IU/ml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…In our study, we found decreased production of IFN-γ in the mitogen tube in 8 out of 10 cases. An altered immune response will lead to an insufficient reaction in the mitogen tube, corresponding to the incapacity of lymphocytes to secrete IFN-γ 46 54–58. Possibly, the T lymphocytes among the participants with indeterminate results were compromised in quality and were thus unable to produce sufficient levels of IFN-γ 46 57.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found decreased production of IFN-γ in the mitogen tube in 8 out of 10 cases. An altered immune response will lead to an insufficient reaction in the mitogen tube, corresponding to the incapacity of lymphocytes to secrete IFN-γ 46 54–58. Possibly, the T lymphocytes among the participants with indeterminate results were compromised in quality and were thus unable to produce sufficient levels of IFN-γ 46 57.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of tuberculosis disease (TB), the QFT-TB assay lacks of sensitivity with many indederminate results. These are related to an alteration of the mitogen response ( 62 ) and are encountered in patients where T-cells exhaustion is frequent. Comparative sensitivity and specificity analysis of T-cell assays to SARS-CoV-2 is not available, however, we did not find any such indeterminate result for QFT SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…An altered immune response will lead to an insufficient reaction in the mitogen tube, corresponding to the incapacity of lymphocytes to secrete IFN-γ. [46,[54][55][56][57][58] Possibly, the T lymphocytes among the participants with indeterminate results were compromised in quality and were thus unable to produce sufficient levels of IFN-γ. [46,57] In support, most of the participants with indeterminate results had been on ART for less than a year, all were ambulatory, and none had a known illness other than HIV.…”
Section: Discussionmentioning
confidence: 99%
“…In cases of immune suppression, repeat testing is advised after recovery. [54, 55] Further, with indeterminate results, TB infection cannot be ruled out with certainty, and the prognosis may be poorer. [54, 55] The increased response in the Nil tube found in three participants may signify residual IFN-γ due to ongoing infection, [58] and TB infection could not be ruled out.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation